The Prosecutor's Office of the Republic of Uzbekistan: A Philosophical Analysis of Its History, Current Role, and Objectives - Xoliyarova, Mahbuba (Pubmedia Social Sciences and Humanities, 2024)
This paper explores the philosophical, historical, and legal evolution of Uzbekistan's Prosecutor's Office, tracing its roots from ancient concepts of justice through Soviet influence to modern democratic ideals. Emphasising its dual role as a guardian of the law and a moral custodian, the study analyses the Office’s trajectory from a Soviet-era mechanism of control to an institution aligned with the democratic aspirations of an independent Uzbekistan. Through a comparative historical analysis, the research highlights significant stages of development, including the Soviet period's impact on judicial independence and subsequent post-independence reforms aimed at increasing transparency, accountability, and alignment with democratic standards. Additionally, this paper discusses the Prosecutor's Office’s responsibilities in upholding the rule of law, enforcing public welfare, and fostering social trust. The findings suggest that Uzbekistan’s prosecutorial system has evolved uniquely, reflecting both the nation’s historical legacy and its commitment to global legal principles, thus positioning itself as a robust institution of democratic governance and societal welfare.